Systemic Sclerosis and Lupus: Points in an Interferon-Mediated Continuum - Assassi, Shervin (2010)
OBJECTIVE: To investigate peripheral blood (PB) cell transcript profiles of systemic sclerosis (SSc) and its subtypes in direct comparison with systemic lupus erythematosus (SLE). METHODS: We investigated PB cell samples from 74 SSc patients, 21 healthy controls, and 17 SLE patients using Illumina Human Ref-8 BeadChips and quantitative polymerase chain reaction confirmation. None of the study participants were receiving immunosuppressive agents other than low-dose steroids and hydroxychloroquine. In addition to conventional statistical and modular analysis, a composite score for the interferon (IFN)–inducible genes was calculated. Within the group of patients with SSc, the correlation of the IFN score with the serologic and clinical subtypes was investigated, as were single-nucleotide polymorphisms in a selected number of IFN pathway genes. RESULTS: Many of the most prominently overexpressed genes in SSc and SLE were IFN-inducible genes. Forty-three of 47 overexpressed IFN-inducible genes in SSc (91%) were similarly altered in SLE. The IFN score was highest in the SLE patients, followed by the SSc patients, and then the controls. The difference in IFN score among all 3 groups was statistically significant (P < 0.001 for all 3 comparisons). SSc and SLE PB cell samples showed striking parallels to our previously reported SSc skin transcripts in regard to the IFN-inducible gene expression pattern. In SSc, the presence of antitopoisomerase and anti–U1 RNP antibodies and lymphopenia correlated with the higher IFN scores (P = 0.005, P = 0.001, and P = 0.004, respectively); a missense mutation in IFNAR2 was significantly associated with the IFN score. CONCLUSION: SLE and SSc fit within the same spectrum of IFN-mediated diseases. A subset of SSc patients shows a “lupus-like” high IFN-inducible gene expression pattern that correlates with the presence of antitopoisomerase and anti–U1 RNP antibodies.